Pengukuran Zoho Books berdasarkan metode Functionality, Usability, Performance, Reliability dan Supportability - Graciella Prayitna (Universitas Teknokrat Indonesia, 2024)
This research evaluates Zoho Books software by measuring the Functionality, Usability, Performance, Reliability dan Supportability aspects. The research objective was to assess the capabilities, ease of use, and performance of Zoho Books in meeting the accounting needs of small to medium businesses. Research methods involve feature analysis, user testing, and measuring application response in a controlled environment. The research results show that Zoho Books has complete features that cover the entire accounting cycle, an intuitive interface despite limited customization, and responsive performance thanks to cloud technology. In conclusion, Zoho Books is a reliable and efficient tool for accounting management, but there is still room for improvement in terms of interface flexibility.